2015
DOI: 10.1021/acs.jpcc.5b03491
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Charge Mobility in Individual Conjugated Polyelectrolyte Nanoparticles Revealed by Two-Color Single Particle Spectroelectrochemistry Studies

Abstract: The optoelectronic properties of conjugated polymers and conjugated polyelectrolytes (CPEs) depend on their chain conformation and packing. Correlations between emission color, charge mobility and extent of aggregation in these materials have been previously established from bulk studies. Here we describe the preparation of stable nanoparticle suspensions of the CPE poly[5-methoxy-2-(3-sulfopropoxy)-1,4-phenylenevinylene (MPS-PPV) where changes in the solvent composition enable tuning their emission spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
(170 reference statements)
0
7
0
Order By: Relevance
“…45 Very recently, a report by Godin et al described the fluorescence enhancement of MPS-PPV prepared in different solvent mixtures (H 2 O/THF). 46 In low water content, nanoparticles (110-212 nm) exhibited a redshift in the emission which was also attributed to the increase in the conjugation length of MPS-PPV.…”
Section: Fluorescence Enhancementmentioning
confidence: 92%
“…45 Very recently, a report by Godin et al described the fluorescence enhancement of MPS-PPV prepared in different solvent mixtures (H 2 O/THF). 46 In low water content, nanoparticles (110-212 nm) exhibited a redshift in the emission which was also attributed to the increase in the conjugation length of MPS-PPV.…”
Section: Fluorescence Enhancementmentioning
confidence: 92%
“…Whether dissolved in hydrophobic or hydrophilic media, their fluorescence emission dramatically changes. [23][24][25] In particular phenylene based polymers exhibit a pronounced spectral emission shift when going from the aggregated to the free chain. 26 As such, they have been employed as piezochromic probes 27 and membrane reporters.…”
mentioning
confidence: 99%
“…Interfacial and intracellular redox states and processes have been extensively explored using fluorescent probes of redox proteins and dyes, where mapping redox potentials (times) of interfacial and intracellular electron transfer processes in chemical and biological systems have become feasible due to recent technological developments. In contrast to conventional single-molecule confocal fluorescence microscopy, which only detects one single molecule at a time due to its limitation of a single point photon detector, single-molecule localization super-resolution fluorescence microscopy allows simultaneous fluorescence monitoring of multiple single molecules in the field of view by high-speed camera with high sensitivity, and thereby hundreds of single-molecule fluorescence intensity trajectories can be acquired with high throughput. For more than a decade, single-molecule fluorescence microscopies have been combined with electrochemical modulation to develop single-molecule spectroelectrochemistry at single-molecule levels and nanoscales. For example, heterogeneous charge mobility of individual conjugated polyelectrolyte nanoparticles was studied in organic solvent via two-color single particle spectroelectrochemistry; Jin et al reported the direct observation and quantitative analysis of single redox events of resorufin to the nonfluorescent dihydroresorufin via electrochemical modulation inside silica nanochannels . The modulation of the fluorescence as a function of electrochemical potential of the fluorescent dye Alexa Fluor 647 conjugated to bovine serum albumin was studied by total internal reflection fluorescence microscopy .…”
Section: Introductionmentioning
confidence: 99%
“…reviewed single-molecule fluorescence microscopy for probing the electrochemical interface . When the single-molecule fluorescence microscope is coupled with electrochemical potential scanning, every redox-active single fluorescent molecule is expected to be laid out in an electrochemically modulated fluorescence intensity (vs time) trajectory. However, photodriven processes also cause single molecule fluorescence intensity fluctuations, which disguise the electrochemically driven fluorescence intensity changes. In other words, it is difficult to tell the electrochemically modulated fluorescence change apart from other causes of fluorescence on/off blinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation